Efecto del promotor orgánico "Natural Growth" en la germinación y desarrollo de Tectona grandis L.f. (teca) Ochroma pyramidale (Cav. ex Lam.) Urb. (balsa), Gmelina arborea Roxb (melina) y Schizolobium parahybum(Vell.) S.F. Blake (pachaco) a nivel de vivero en Moraspungo, provincia de Cotopaxi. - Palacios Riera, Danny Alejandro (2021)
The present research was able to determine the effect of the organic promoter "Natural Growth" in four forest species (T. grandis, O. pyramidale, G. arborea and S. parahybum) at the nursery level, given by two stages, the first was by pregerminative treatment and the second by the evaluation of the morphometric variables applying concentration doses of 37.5 and 62.5 m3 of the organic product, so that in the growth and development of the species it was possible to make the estimation of the height variables; diameter, leaf width, root length, foliar dry weight, root dry weight, etc. Data collection was obtained every 15 days during two months of research. Within the statistical analysis, it is possible to determine a greater incidence in the results with the organic product being effective for growth, pest prevention and also acts as a soil activator, in addition, investigations of other non-forest species have already been done giving incredible results in their harvests, in short, this product has had success in Ecuador applied in crops of short and long cycles, and in other parts of the world, being a product recognized by many farmers. Keywords: Diameter, fresh and dry weight, height, root length, seedlings.